ANALISIS KOMPONEN RBBR TERHADAP HARGA SAHAM PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI TAHUN 2013 – 2017 - Panjaitan, Raya; Silalahi, Andri D. K. (UNIKA Santo Thomas, 2020)
This study aims to analyze the effects of Risk Based Bank Rating components on company stock prices. The Risk Based Bank Rating (RBBR) components consist by LDR, GCG, ROA and CAR. Secondary data was uses in this study with numbers of samples 196 consisting by 42 companies and 3 years financial report. Multiple linear regression was used to analyze the data. The result shows that LDR and GCG have negatively and significantly affected to stock prices. ROA has positively and significantly affected price stock. CAR has positively but insignificantly affected the price stock. Simultaneously, LDR, GCG, ROA and CAR have positively and significantly affected price stock. For further research using other variables related to analyzing the price stock are suggested to use.